SHM_148789_HST_3D Bronze Age Flanged Axe with Incised Parallel Lines from the Pile Hoard - National Historical Museums (National Historical Museums, 2026)
Structure from motion (SfM) 3D model of a Bronze Age flanged axe with incised parallel lines from the Swedish Late Neolithic or Early Bronze Age. Collected from Pile in Tygelsjö parish in the prvince of Skåne, Sweden, in 1864 as part of a larger hoard deposit, it is now held in the collections of the National Historical Museums in Stockholm.

Link to the Dynamic Collection platform

https://dyncoll.ht.lu.se/artifact_view.php?item=1001

Link to Sök I Samlingarna

https://samlingar.shm.se/object/394F1F22-90D1-42F0-9774-1B766275C7C5
Keywords: Archaeology; Archaeology; Archaeology/history; Dynamic Collections; 3D Model; Museum Object; Pile; Swedish Bronze Age; Swedish Late Neolithic; Structure from Motion; SfM; History and Archaeology; Historia och arkeologi; Archaeology; Arkeologi